Comparison of Imipenem prescription model in Imam Khomeini and Taleghani Educational Center of Urmia - Maryam Divanbeygi (Tehran University of Medical Sciences, 2024)
Introduction: Drug utilization evaluation (DUE) studies are designed to evaluate the rational use of drugs. Our purpose in this study is to evaluate the pattern of Imipenem, a broad-spectrum antibiotic used in different parts of Imam Khomeini and Taleghani Educational Center of Urmia. Method and material: This is a cross-sectional and retrospective study. The study was conducted by reviewing medical records of 200 admitted patients who received Imipenem during March 2016 to 2017. Results: In the study Imipenem was prescribed most frequently for intra-abdominal infection in 71 cases (35.5%), 41cases (20.5%) respiratory infection, 31 cases (15.5%) urinary tract infection, 25 cases (12.5%) skin infection, 15 (7.5%) cases septicemia infection, 7 (3.5%) cases bone and neutropenic infection, endocarditis infection were reported in 3 cases (1.5%). The highest incidence was related to intra-abdominal infections. 61% of Talehgsni hospital patients and 46% of Imam Khomeini hospital patients received Imipenem less than a week. The used dose in all patients was between one to four grams per day and the frequency of use was not correct in 7% of Taleghani hospital patients and 23% of patients in Imam Khomeini hospital. Conclusion: Some AB combination was proved to be inappropriate to the guidline consedering the indication or the microorganism to be covered. It is necessary to take action to improve prescribing habit in order to reduce the unnecessary usage of antibiotic thus enhance rational antibiotic use.